Narrow Linewidth Excitonic Emission in Organic–Inorganic Lead Iodide Perovskite Single Crystals - Diab, Hiba; Trippé-Allard, Gaëlle; Lédée, Ferdinand; Jemli, Khaoula; Vilar, Christèle; Bouchez, Guillaume; Jacques, Vincent L.R; Tejeda, Antonio; Even, Jacky; Lauret, Jean-Sébastien; Deleporte, Emmanuelle; Garrot, Damien (The journal of physical chemistry letters, 2016)
Hybrid perovskite thin films have demonstrated impressive performance for solar energy conversion and optoelectronic applications. However, further progress will benefit from a better knowledge of the intrinsic photophysics of materials. Here, the temperature-dependent emission properties of CH3NH3PbI3 single crystals are investigated and compared to those of thin polycrystalline films by means of steady-state and time-resolved photoluminescence spectroscopy. Single crystals photoluminescence present a sharp excitonic emission at high energy, with full width at half maximum of only 5 meV, assigned to free excitonic recombination. We highlight a strong thermal broadening of the free excitonic emission, due to exciton–LO-phonon coupling. The emission turned to be very short-lived with a subnanosecond dynamics, mainly induced by the fast trapping of the excitons. The free excitonic emission is completely absent of the thin film spectra, which are dominated by trap state bands.